Interaction Analysis of Abnormal Lipid Indices and Hypertension for Ischemic Stroke: A 10-Year Prospective Cohort Study - Wei, Lai; Sun, Junxiang; Xie, Hankun; Zhuang, Qian; Wei, Pengfei; Zhao, Xianghai; Chen, Yanchun; Dong, Jiayi; Li, Mengxia; Chen, Changying; Yang, Song; Shen, Chong (Frontiers in Cardiovascular Medicine, 2022)
Background: Dyslipidemia and hypertension are two important independent risk factors for ischemic stroke (IS); however, their combined effect on IS remains uncertain. Objectives: This present study aimed to evaluate the interaction effect of hypertension and abnormal lipid indices on IS in a ten-year prospective cohort in Chinese adults. Methods: The cohort study of 4,128 participants was conducted in May 2009 and was followed up to July 2020. All qualified participants received a questionnaire survey, physical examination, and blood sample detection. Cox regression was used to evaluate the association of dyslipidemia and hypertension with IS, and calculate the hazard ratio (HR) and 95% confidence interval (CI). The relative excess risk of interaction (RERI) and the HR (95%CI) of interaction terms were used to examine additive and multiplicative interactions. Results: In the hypertensive population, Non-HDL-C ≥ 190 mg/dl, LDL-C/HDL-C ≥ 2 and HDL-C ≥ 60 mg/dl were statistically associated with IS, and after adjusting for covariates, HRs (95%CIs) were 1.565 (1.007-2.429), 1.414 (1.034-1.933) and 0.665 (0.450-0.983), respectively. While in the non-hypertension population, no significant association of Non-HDL-C ≥ 190 mg/dl, LDL-C/HDL-C ≥ 2, and HDL-C ≥ 60 was detected with IS (P >0.05). There was a significant association between TC/HDL-C ≥ 3.6 and the decreased risk of IS in the non-hypertension population, and the HR (95%CI) was 0.479 (0.307-0.750). Whereas, a similar association was not observed in the hypertensive population. HDL-C ≥ 60 mg/dl, Non-HDL-C ≥ 190 mg/dl, TC/HDL-C ≥ 3.6, and TG/HDL-C ≥ 1 have additive and multiplicative interactions with hypertension (P<0.05). The RERIs (95% CIs) of the additive interaction are -0.93 (-1.882–0.044), 1.394 (0.38-2.407), 0.752 (0.354-1.151) and 0.575 (0.086-1.065), respectively. The HRs (95% CIs) of the multiplicative interaction terms were 0.498 (0.272-0.911), 4.218 (1.230-14.464), 2.423 (1.437-4.086) and 1.701 (1.016-2.848), respectively. Conclusions: High concentration of HDL-C reduces the impact of hypertension on IS, while the high concentration of Non-HDL-C, TC/HDL-C, and TG/HDL-C positively interact with hypertension affecting the incidence of IS. This study provides useful evidence for the combined effects of dyslipidemia and hypertension in predicting IS.